Effect of Cryopreserved Bone Marrow Transplantation on Dynamics of Recovery of Morphofunctional Properties of Lymphoid, Myeloid and Endocrine Organs in Lethally Irradiated Recipients - Tsutsayeva, A. A.; Chernousova, S. S.; Glushko, T. A.; Shatilova, L. E.; Volina, V. V.; Sokol, L. V.; Ivakhnenko, L. Yu.; Chernyshenko, L. G.; Brovko, E. V. (Problems of Cryobiology and Cryomedicine, 2009)
There was realised a combined study of morphofunctional properties of lymphoid, myeloid and endocrine organs in lethally irradiated mice at different stages after cryopreserved syngeneic bone marrow (CSBM) cell transplantation. The CSBM cell transplantation to lethally irradiated animals demonstrated the stimulation of recovery processes in neurohumoral organs. At the same time the wave-like changes in triiodothyronine (T3), thyroxin (T4), corticosterone and insulin hormone levels in peripheral blood, even if not reaching the level of physiological norm, provide the survival within 3 months for lethally irradiated animals, dying without transplantation to the 10th day.